Evaluating the Impact of a Structured Teaching Programme on Knowledge About Endometriosis Among First-Year Degree Students in a Chosen College in Wayanad District - Aleena Mathew; Aleena Renny; Aleena Thomas; Alen Sebastian; Andrea Eldhose; Anilda Sunny; Mithu Joy (International Journal of Midwifery Nursing And Practices, 2024)
Introduction: The primary objective of this study is to evaluate the impact of a structured teaching program on the understanding of endometriosis among female students enrolled in the first year of a chosen degree arts and science college in Wayanad district. The specific goals include evaluating the baseline knowledge about endometriosis among first-year degree students in the selected college and determining the effectiveness of the structured teaching program in enhancing their knowledge on this subject. Materials and Methods: A quantitative approach was utilized in the implementation of a pre-test post-test study design. 100 female students who are between the age group of 18 and 20 years and who are studying in first year degree course were selected by convenient sampling technique. Tools used were socio demographic per forma and self-structured knowledge questionnaire on endometriosis. After obtaining formal permission from authority concerned, structured questionnaire was used to collect the needed data. Data collection took place between September 26, 2022, and September 30, 2022. The initial assessment, or pre-test, was conducted on the first day, and immediately thereafter, the structured teaching program was administered on the same day. The post-test was conducted 1 week later. Subsequently, the data were collected, tabulated, and analysed using both descriptive and inferential statistics. Results: The results were as follows: among the 100 samples, 3% had good knowledge and 45% had average knowledge, 54% had poor knowledge before the educational intervention. On the other hand, 50% of the samples had excellent knowledge ,45% have good knowledge and rest 5% have average knowledge after educational intervention. The result suggests that the research hypotheses H1 is accepted. The study indicates that the average pretest score was 6.30±2.47, while the mean post-test score was 16.04±2.34. The effectiveness of the structured teaching program on endometriosis knowledge is demonstrated by the results. This suggests accepting the research hypothesis H2.
Keywords: educational intervention; effectiveness; endometriosis; structured teaching program